Planning for the Development of Bulletin Board Media to Increase Students' Learning Motivation in Pancasila Education Subjects in Junior High School - Rahmi Parianti; Evy Ratna Kartika Waty; Umi Chotimah (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze the need for developing bulletin board media to increase students' learning motivation in Pancasila Education subjects in junior high school. From the observation of 32 learners in class VII SMP N 6 Lahat, it was found that 10 learners often came late, had not taken out books and Learner Worksheets (LKPD) after the lesson started, paid less attention to the teacher's explanation, and did not carry out the teacher's orders. The results of the daily test showed that only 19 students were complete in achieving the material, while 13 others were not complete. This shows that the material tested has not been mastered well by students. In addition, the delivery of material by teachers is still monotonous, traditional, and minimal learning media. The percentage of PKN learning completeness only reached 59%, while the other 41% were not complete. So this research emphasizes the importance of further development of bulletin board media as a means to increase student motivation and learning outcomes.